Employee Sleep Enhancement and Fatigue Reduction Programs: Analysis of the 2017 CDC Workplace Health in America Poll. Issue 4 (May 2021) - Robbins, Rebecca; Weaver, Matthew D.; Quan, Stuart F.; Rosenberg, Elliot; Barger, Laura K.; Czeisler, Charles A.; Grandner, Michael A.
Background: Poor sleep health, including sleep deficiency and sleep disturbance, is common among employed adults in the U.S. and is associated with undesirable workplace outcomes. Adoption of workplace health promotion programs (WHPPs) is increasing, yet few programs aim to reduce fatigue or improve sleep among employees. Objective: We analyzed data from the nationally representative 2017 Centers for Disease Control Workplace Health in America poll to identify the prevalence of sleep enhancement or fatigue reduction WHPPs and the characteristics of employers that offer these programs. Method: A stratified random sample of nationally-representative worksites with ≥10 employees was generated. It comprised 2, 843 worksites. Worksite representatives reported workplace characteristics, health promotion activities, and the likelihood of offering WHPPs relating to sleep enhancement or fatigue reduction. Logistic regression analyses were utilized to identify characteristics associated with offering a sleep enhancement or fatigue reduction WHPP, controlling for WHPP budget and size of the company, and contingent on worksites having a comprehensive workplace health plan. Results: Less than 1 in 10 worksites (10%) reported offering a sleep enhancement or fatigue reduction WHPP. Worksites most likely to offer a sleep-focused WHPP were those in retail, wholesale, or technology industries (OR = 2.71, 95%CI: 1.08-6.8) vs. those in the finance, information, technology industries; those with a large WHPP budget (>$500, 000, OR = 6.85, 95%CI: 2.1-22.35) vs. those with no budget; and those that had visible support of WHPP initiatives from senior leadership (OR = 4.74, 95%CI: 1.91-11.75) vs. those without such support. Conclusions: Our results highlight how few worksites reported offering sleep-focused programs for their employees. Those worksites that did feature such programs, were commonly well-resourced and had senior leadership support for WHPP initiatives in general. Future research should consider working directly with leaders to expand the implementation of employee sleep enhancement and fatigue reduction WHPPs.